ANALISIS FAKTOR-FAKTOR KEPUASAN SISWA SMA SANTA MARIA KABANJAHE KECAMATAN KABANJAHE KABUPATEN KARO SUMATERA UTARA - Ingan Ukur Br Sitepu (JURNAL REGIONOMIC, 2020)
The era of globalization, this research aims to find out which factors increase the level of student satisfaction. The number of studies was 392 students. The sample of this study was calculated with the Slovin formula of 100 respondents. The sample chosen by stratified sampling technique is the sample selection technique by taking a sample by taking into account the strata (assessment) in participation. Data collection using a questionnaire. The analytical method used is multiple linear regression.The results of the study prove that physical evidence, reliability, responsiveness, and empathy support partial to student satisfaction, while the Guarantee variable does not significantly influence student satisfaction. Variables of physical evidence, reliability, responsiveness, assurance, and empathy are simultaneously guaranteed to Student Satisfaction. The results determine the facts received by students by physical proof factors, reliability, responsiveness, assurance, and empathy.